Electric Conductivity and Piezoresistivity of Carbon Nanotube Artificial Skin Based on the Design of Mesh Structure - Xin Ma; Wen Li; Liting Wang; Xiaona Cao (Advances in Materials Science and Engineering)
This paper introduces a new method of sensing pressure by using carbon nanotube yarns which are embedded in artificial skin, based on the design of the mesh structure. With the sensing technology, a kind of mesh model has been established for piezoresistive effect detection of carbon nanotube yarns in artificial skin. By analyzing the sensing characteristics of carbon nanotube yarns, we can conclude that the artificial skin embedded with yarns in a mesh model could be used for sensing pressure. It may cover the surface of the robot and has significant theoretical as well as practical value for intelligent robot research in the future.